PERBANDINGAN KANYOUKU BAHASA JEPANG DAN BABASAN BAHASA SUNDA YANG MENGANDUNG KATA 'KEPALA' DAN 'WAJAH (KAJIAN SEMANTIK) - Audi Sudiyana, - (2018)
The purpose of the study was to describe the comparison between Japanese kanyouku and Sundanese babasan which contain 'head' and 'face' words. The study used descriptive method. The techniques used in the study were literature study technique and interpretation technique. From the data that had been collected, there have been seven Japanese kanyouku and six Sundanese babasan of 'head' words, and eleven Japanese kanyouku and eight Sundanese babasan of 'face' words. From the data, it was found the similarities and differences in meaning changes and meaning extension. In Japanese kanyouku, the word of 'atama' (head) has meaning change into limits of power; thinking ability or intelligence and stupidity; ulyielding attitude; arrogant; and showing calm and peaceful soul, but in Sundanese babasan, the word of 'hulu' (kepala) has meaning change into pride, arrogant, unclear attitude or thinking / confused. In Japanese kanyouku, the word of 'kao' (face) has meaning change into pride, shame / confident and arrogant, but in Sundanese babasan, the word of 'beungeut' (face) shows pride, shame and no-self awareness. In meaning extension, the two forms of idiom are formed as metonimia, methapor, sinekdok and simile. Simile masters is only found in the Sundanese idiom of 'beungeut' word. Finally, hopefully the results of this study can enrich the treasure of comparison knowledge and can be used for learning purposes. Key words: comparison, semantic, meaning, kanyouku, babasan